8(x-3)-5(x+2)=6

Simple and best practice solution for 8(x-3)-5(x+2)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-3)-5(x+2)=6 equation:


Simplifying
8(x + -3) + -5(x + 2) = 6

Reorder the terms:
8(-3 + x) + -5(x + 2) = 6
(-3 * 8 + x * 8) + -5(x + 2) = 6
(-24 + 8x) + -5(x + 2) = 6

Reorder the terms:
-24 + 8x + -5(2 + x) = 6
-24 + 8x + (2 * -5 + x * -5) = 6
-24 + 8x + (-10 + -5x) = 6

Reorder the terms:
-24 + -10 + 8x + -5x = 6

Combine like terms: -24 + -10 = -34
-34 + 8x + -5x = 6

Combine like terms: 8x + -5x = 3x
-34 + 3x = 6

Solving
-34 + 3x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '34' to each side of the equation.
-34 + 34 + 3x = 6 + 34

Combine like terms: -34 + 34 = 0
0 + 3x = 6 + 34
3x = 6 + 34

Combine like terms: 6 + 34 = 40
3x = 40

Divide each side by '3'.
x = 13.33333333

Simplifying
x = 13.33333333

See similar equations:

| 2x+5x=-14 | | 3x+6-2x-2=0 | | 3(t-3)-2+=-30 | | 0.2x^2-1.2x+0.2=0 | | x-10=6x+9 | | 2x+2x=12 | | 3(t-3)-2=-30 | | -7X+5[X-7]=-27 | | 3(x+2)+50=-4x | | 9+3(5y+3)= | | 4x+7=49 | | -40-8x=10x+22 | | 4x+8=-8-9x | | -6=3(y+2) | | 1/3(x+4)+1/5(x+3)=3 | | 4562= | | 3x+2x=25-15 | | -7x-2x=36 | | 1/5(2x+8)=x+1 | | 6-2x=2(15-x) | | a+5(3-a)=11 | | -9V-5+6V=19 | | (x+10)/3=(x+5)/2 | | 3y+50-5y=70 | | m^2+22m+23=0 | | 1/4(x+6)=1/3(x+4) | | 2x^2+14x+2165=0 | | 265-2x=43x+20 | | 22m+23+m^2=0 | | x/3-3=2 | | D+1=7 | | F=-30 |

Equations solver categories